YOUTHS’ ENGAGEMENT AND THE ATTAINMENT OF DEVELOPMENT PROGRAMMES IN “OLOGUNERU” COMMUNITY, OYO STATE, NIGERIA (Unilorin Journal of Lifelong Education, 2023)
Engagement of community members across board particularly the youths which constitute energy-driven and conscious population is said to be the springboard for the realization of development programmes in the community. It is on this premise that this study examined youths’ engagement and the attainment of community development programmes in “Ologuneru” community, Ido Local Government area, Oyo State, Nigeria. Ex-post-facto research design was adopted for this study and the study population comprised of 4 registered Youths’ Associations’ membership which was 281. Cluster and simple random sampling techniques were used to select 141 respondents. Structured Questionnaire with r = 0.087 was used for data collection. Data collected were analyzed using: Frequency counts, Percentages, Mean score, Standard deviation and Pearson Product Moment Correlation Co-efficient. It was found that Youths’ engagement in development programmes have significant positive impacts on the attainments of community development programmes. Based on the findings, the study recommends that; fatalistic attitudes of the Adults and constraints towards Youths’ engagements should be addressed as well as constants recognition of youths’ population in the scheme of development agenda for uppermost attainment of development programmes in the community.